The impact of digital communication and offline social interactions on depressive symptoms in Chinese older people - Chai, Qi; Yang, Zhengting; Luo, Yiting; Deng, Yin; Qin, Lu; Yang, Zhibo; Wang, Ruizhi; Zhou, Yongzhao (Frontiers in Public Health, 2024)
BackgroundIn a special period of lack of offline social interaction (pandemic), the mentality of older people is changing quietly. This study aims to dissect the impact of these changes on their mental health.MethodUtilizing data from the China Health and Retirement Longitudinal Study (CHARLS 2020), this research included 7,784 participants aged over 60 years. It evaluated the prevalence of depressive symptoms, and assessed the relative effects of these interactions on depressive symptoms.Results(1) a depressive symptom prevalence of 40.65%; (2) a modest engagement in digital communication, with only 20.39% of the older participating; (3) varying prevalences of depressive symptoms across groups, with notable differences depending on the type and combination of social interactions. Specifically, the prevalence was 21.7% among those engaging only in digital communication, and varied from 21.7 to 32.0% among other groups, highlighting the significant impact of social interaction patterns on depressive symptoms. Statistical analysis confirmed the significance of these findings (χ2 = 42.415, p < 0.001). (4) In the first model, digital communication was associated with a lower likelihood of depressive symptoms (OR = 0.820, 95%CI: 0.707–0.950, p < 0.05). The second model showed no significant effect of offline social interactions on depressive symptoms (OR = 0.124, 95%CI: 0.917–1.143, p = 0.678). The third model demonstrated that the inclusion of offline social interaction variables did not significantly alter the beneficial effect of digital communication (OR = 0.820, 95%CI: 0.707–0.952, p < 0.05). (5) The results of the 1:1 matching analysis indicated that digital communication significantly alleviated depressive symptoms in older people (ATT = −0.054, p < 0.05). Conversely, offline social interactions did not significantly affect the depressive symptoms of this demographic (ATT = −0.028, p > 0.05).ConclusionThe depressive symptoms among older people in China has greatly increased during 2020 which year the COVID-19 pandemic was in the early stage, accompanied by considerable changes in their modes of social interaction. Our findings suggest that the influences of digital communication and offline social interactions on depressive symptoms may have operated independently during the pandemic. The potential of digital communication engagements in enhancing mental health, particularly in exceptional circumstances such as during a pandemic, underscores the need for further exploration.